Bibliometric Analysis: Acceptance and Commitment Therapy on Post Traumatic Stress Disorder - wahidin, Wahidin; Said, Faridah Binti Mohd; musheer, Musheer; Sari, Rina Oxtafia Sari (International Journal Labs, 2024)
The study carried out a bibliometric analysis of Acceptance and Commitment Therapy on Post Traumatic Stress Disorder to know the effectiveness of the therapy. This bibliometric research focuses on looking at research activities around the world using publication data from the Scopus database. Bibliometric analysis uses a quantitative approach to analyze results and provide a representative picture. This research is recognized as a practical approach to assessing the output of publications, organization, writing, and characteristics of research topics between 2005 until 2023. There are Attempts to use Acceptance and Commitment Therapy to reduce trauma but the amount of effort did not increase significantly. Instead, the Acceptance and Commitment Therapy research is growing.